Association of the Urease Gene with Enterohemorrhagic Escherichia coli Strains Irrespective of Their Serogroups - Nakano, Masayuki (American Society for Microbiology, 2001)
Among various diarrheagenic Escherichia coli strains from clinical sources, we found that the urease gene was specifically associated with enterohemorrhagic E. coli (EHEC) strains irrespective of their serogroups. The results suggest that the urease gene can be a useful genetic marker for the detection of EHEC strains and for the diagnosis of infections caused by EHEC strains in the clinical situation.